2017
DOI: 10.1111/ctr.13097
|View full text |Cite
|
Sign up to set email alerts
|

Predictive model and risk factors associated with a revised definition of early allograft dysfunction in liver transplant recipients

Abstract: Higher AST/ALT level needed as cutoff in comparison with the old EAD definition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
0
18
1
Order By: Relevance
“…As persistent uncontrolled coagulopathy be an early sign of transplanted graft dysfunction [74], it is not surprising that the requirement for FFP transfusion was higher in the EAD group than in the non-EAD group. Poor liver graft recovery seems to begin with severe ischemia–reperfusion injury, followed by the continuous presence of coagulopathy [75].…”
Section: Discussionmentioning
confidence: 99%
“…As persistent uncontrolled coagulopathy be an early sign of transplanted graft dysfunction [74], it is not surprising that the requirement for FFP transfusion was higher in the EAD group than in the non-EAD group. Poor liver graft recovery seems to begin with severe ischemia–reperfusion injury, followed by the continuous presence of coagulopathy [75].…”
Section: Discussionmentioning
confidence: 99%
“…As the continuous score validated by single-center, retrospective studies, both MELDPOD5 and MEAF are the formula conversion of several biochemical markers into numerical variables, which might better evaluate the severity of the patient's prognosis after OLT. Several studies have showed that the presence of EAD defined by the Olthoff criteria substantially affects graft and patient outcome (9,18,23). However, it has reported that EAD defined by the Olthoff criteria, which contains ALT and AST as indicators, is controversial in evaluating the prognosis of graft and patient (24).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the liver function of the EAD patients recovers slower, resulting in patients requiring longer intensive care. Correspondingly, hospital stay and ICU time in the EAD patients would increase (21,23,31).…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of early allograft dysfunction (EAD) was defined according to the updated criteria designed by Nicolau-Raducu et al before (19). To be specific, patients who met the following items simultaneously within the first week after liver transplantation including: (I) ALT >3,000 IU/mL or AST >6,000 IU/mL; (II) total bilirubin (TB) ≥10 mg/dL; (III) international normalized ratio (INR) ≥1.6 was diagnosed as EAD (19). And diagnostic criteria of PNF was defined as non-recoverable liver function necessitating emergency retransplantation within the first 72 hours after LT (20).…”
Section: Definition For Several Concept Of Complicationsmentioning
confidence: 99%
“…And the peak value for AST level in non-steatosis group was about 55% lower than the correspond value in MaS group (2,178 vs. 4,839 U/L, P<0.05). According to criteria(19) defined before, EAD was occurred in 41 patients (accounting for 16.7% of whole patients). Compared to patients in steatosis group, EAD occurrence in non-steatosis group was much lower than steatosis group (10.7% vs. 22.8%, P<0.05).…”
mentioning
confidence: 99%